An assessment of technical issues raised in R.W. Haley's critique of three studies of health effects of the Gulf War - Haggstrom, Gus W.; Rand eBooks (Santa Monica, CA : RAND, 2000)
In a 1998 article published in the American Journal of Epidemiology and in a reply to counterpoints by the original authors of the studies, R.W. Haley challenged the validity of three government-sponsored studies that found no increased risk of adverse health effects in American veterans of Operation Desert Storm and Operation Desert Shield. This report examines the statistical methods used by the authors of the original studies and Haley's charges of statistical "bias" and concludes that the earlier studies were scientifically valid.
"National Defense Research Institute."
"This work ... was carried out jointly by RAND Health's Center for Military Health Policy Research and the Forces and Resources Policy Center of the National Defense Research Institute"--Preface.
Includes bibliographical references (p. 15).
Also available on the internet via WWW in PDF format.
Keywords: Persian Gulf syndrome -- Research -- Statistical methods; Persian Gulf syndrome -- United States; Persian Gulf War, 1991 -- Health aspects -- United States; Persian Gulf War, 1991 -- Veterans -- Diseases -- United States; Veterans -- Diseases -- United States; Electronic books